Milk productivity of holstein cows at optimization of fat levels in their diets. Issue 1 (December 2021) - Petrov, O; Semenov, V; Alekseev, V
Abstract: The work is devoted to determining the optimal level of fat in concentrate-senage diets for high-yield cows and studying the effect of various levels of fat in the dry matter of the diet on milk productivity and chemical composition of milk. Studies have shown the insufficiency of household diets of highly productive cows with a dry diet content of 3.2% raw fat. This deterred the potential for dairy productivity. Addition of fat in cow diets by equivalent energy and protein replacement of a portion of the compound feed with a rapeseed cake up to a level of 4.2% of the dry substance provides an increase in milk productivity in relation to the control group receiving 3.2% fat. Optimization of the fat level in the dry substance of the diet up to 4.2% in the nutrition system of cows increases the functional activity of the breast in their body, which is expressed in the growth of breast productivity by 6.78%, improvement of the chemical composition and technological properties of milk. A further increase in dietary fat to 5.2% has a less pronounced effect on the change in milk productivity.